Algorithmic Adjudication and the Erosion of Due Process: Legal Challenges in the Integration of Artificial Intelligence within Digital Justice Systems - Adilova , Marjangul (GLOBAL SCIENTIFIC CONFERENCE ON MULTIDISCIPLINARY RESEARCH, 2026)
The rapid integration of artificial intelligence (AI) and machine learning algorithms into judicial architectures precipitates an unprecedented epistemological crisis within procedural law. While digital justice initiatives promise unparalleled administrative efficiency, the deployment of proprietary algorithmic systems for risk assessment and automated decision-making frequently circumvents established constitutional safeguards. This empirical legal study evaluates the friction between algorithmic utility and fundamental due process rights, specifically focusing on the "black box" transparency deficit. Utilizing a mixed-methods jurimetric approach, the research analyzes a dataset of 350 appellate cases (2019–2024) where algorithmic risk assessments directly influenced pre-trial detention, sentencing, or automated administrative penalties across transitional and consolidated digital jurisdictions. The quantitative synthesis indicates a severe procedural vulnerability; AI-assisted rulings faced appellate challenges primarily targeting algorithmic opacity in 41.5% of the observed cases. Detailed demographic cross-tabulation revealed that predictive justice tools generated a 19.8 ± 3.2% higher rate of false-positive risk scores for marginalized socioeconomic brackets, demonstrating the codification of historical human bias into seemingly objective mathematical models. The inability of defendants to cross-examine proprietary algorithms systematically violates the right to a fair trial. Addressing this legal asymmetry requires abandoning unregulated technological adoption. The paper proposes the statutory implementation of an "algorithmic explainability" standard, mandating that no machine-generated legal inference be admitted into a judicial proceeding without open-source, mathematically verifiable auditing mechanisms accessible to all litigating parties.